Community Service Initiatives: Promoting Education about Justice for Parents and Children - Priyashini Rajhab (Pusat Studi Pembangunan dan Pemberdayaan, 2023)
Community empowerment and justice education are just two of the many topics covered on this page concerning the work of Promoting Education about Justice for Parents and Children. Volunteer programs that teach children and their parents about social justice are crucial in creating communities where people experience a sense of agency, fairness, and social consciousness. These initiatives intend to educate both parents and children on the importance of justice in all parts of daily life, as well as on the rights and responsibilities that come with them. Researched in this article is the impact that community service programs that teach parents and children about justice have on individuals and their surrounding neighborhoods. Furthermore, it explores the various strategies and methods utilized by such programs, including but not limited to workshops, seminars, and various types of community engagement. The article also addresses challenges faced by community service organizations and offers recommendations on how they might be overcome to make their activities as successful as possible. This article examines the impact that community service has on teaching both parents and children about the importance of creating a just and equitable society through cooperation between communities, schools, and service providers. In particular, this study will examine how community work might help teach kids and their families about social justice.